"Care … about physical activity" in care homes in Scotland. Issue 3 (2nd September 2014) - A. Macintosh, Edith; Laventure, Bob
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to outline an approach being taken, to improve opportunities and increase levels of physical activity amongst residents in care homes in Scotland, which has the potential to make a significant difference to the quality of lives. The approach is designed to raise awareness about the importance of physical activity, increase skills, knowledge and capacity amongst the workforce. Design/methodology/approach – The paper describes the reasons for promoting physical activity in care homes. It describes the challenge to this, associated issues and introduces you to a resource pack which offers solutions to care homes through a self-improvement process. It provides a case study which exemplifies how the ideas can be applied on a day-to-day basis. Findings – The paper provides insights into the challenges in the care home sector to promoting physical activity and offers some ways round these. It describes two strategies within the new resource pack to support care home residents to make person centred physical activity choices. Practical implications – This paper suggests that to promote physical activity in a care home the choices and needs of an individual must be the starting point. It requires partnership working and good leadership where staff have the permission to work in a new way. It suggests that risk enablement is key and the benefits of physical activity outweigh the risks even with frail older people. Originality/value – This paper promotes a new resource pack for care homes in Scotland for promoting an active life based on a self-improvement process.